Glutathione as a Semen Additive to Improve Surti Buffalo (Bubalus bubalis) Bull Semen Cryopreservation - Kumar, Kailash; Gaur, Mitesh (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
The present study evaluated the effects of glutathione as an additive in Tris fructose egg yolk citrate extender on Surti buffalo bull semen.  Extended semen @ 80 million sperm/mL was divided into 4 equal aliquots and glutathione was added at 0.5 mM (T1), 2.0 mM (T2), and  5.0 mM (T3) with one control (T0) group. The percentages of post-thaw sperm progressive motility, live sperm, and HOS responsive  sperm were significantly higher (p
Keywords: Cryopreservation; Glutathione; Post-thaw quality; Surti buffalo; Semen additive